2021
DOI: 10.3390/ijms22157933
|View full text |Cite
|
Sign up to set email alerts
|

Differential Proteomic Analysis of Astrocytes and Astrocytes-Derived Extracellular Vesicles from Control and Rai Knockout Mice: Insights into the Mechanisms of Neuroprotection

Abstract: Reactive astrocytes are a hallmark of neurodegenerative disease including multiple sclerosis. It is widely accepted that astrocytes may adopt alternative phenotypes depending on a combination of environmental cues and intrinsic features in a highly plastic and heterogeneous manner. However, we still lack a full understanding of signals and associated signaling pathways driving astrocyte reaction and of the mechanisms by which they drive disease. We have previously shown in the experimental autoimmune encephalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Montecchi et al showed recently that, as well as oligodendrocytes, astrocytes may play a key role in the pathogenesis of MS, mainly in the processes behind neurodegeneration. They identified Rai, a key signaling molecule in the answers of astrocytes to the Th17 cell response to play an important role in neurotoxic effects through, as of yet, largely unknown pathways [119]. Its upregulation is suggested to be an important factor in influencing the proteasome-ubiquitin system, the main pathway of protein degradation in humans (and every mammalian species) [119].…”
Section: Results Of Proteomic Studies In the Research Of Multiple Scl...mentioning
confidence: 99%
See 1 more Smart Citation
“…Montecchi et al showed recently that, as well as oligodendrocytes, astrocytes may play a key role in the pathogenesis of MS, mainly in the processes behind neurodegeneration. They identified Rai, a key signaling molecule in the answers of astrocytes to the Th17 cell response to play an important role in neurotoxic effects through, as of yet, largely unknown pathways [119]. Its upregulation is suggested to be an important factor in influencing the proteasome-ubiquitin system, the main pathway of protein degradation in humans (and every mammalian species) [119].…”
Section: Results Of Proteomic Studies In the Research Of Multiple Scl...mentioning
confidence: 99%
“…They identified Rai, a key signaling molecule in the answers of astrocytes to the Th17 cell response to play an important role in neurotoxic effects through, as of yet, largely unknown pathways [119]. Its upregulation is suggested to be an important factor in influencing the proteasome-ubiquitin system, the main pathway of protein degradation in humans (and every mammalian species) [119]. Their latest assessment showed that Rai knock-out EAE murine astrocytes are able to survive oxidative stress, that the IL-17 dependent expression of hypoxia-inducible factors-1α is inhibited in these astrocytes and that extracellular vesicles of these cells produced as the result of IL-17-stimulus may provide defense against oxidative stress to other "bystander" cells [119].…”
Section: Results Of Proteomic Studies In the Research Of Multiple Scl...mentioning
confidence: 99%
“…The growing literature on HIF shows its importance as a key regulator of immune cell function [52]. HIF1α plays an important role in astrocytes reaction [53]; however here, its beneficial functions might be prevented by the digoxininduced downregulation of its pathway.…”
Section: Discussionmentioning
confidence: 97%
“…These results first confirm the good isolation of EVs as any or very few contaminants, such as highly abundant protein species normally present in common biological fluids, are visible in the vesicular 2DE maps; secondly, they underline the strong divergent protein content between the whole biological sample and the derived EVs. Remarkably, other proteomic analyses conducted by our research group highlighted how the vesicular protein cargo is distinct from its original sample: Montecchi et al focused on the differential proteomic analysis by 2DE of murine astrocytes and murine astrocytes-derived EVs [56]. As Figure 2 shows, the 2DE vesicular map (Figure 2A) is clearly different from the proteomic pattern of the cellular culture of origin (Figure 2B) and highly characteristic of its original sample.…”
Section: Proteomicsmentioning
confidence: 89%